Feline ringworm. Interference with the epidemiology of Microsporum canis - BOURDZI-HATZOPOULOU (ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ Ε.) E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The presence of dermatophytes in animals with skin lesions (ringworm), as well as in animals with apparently healthy skin (healthy carriers) was studied. Skin scales and infected hair from 125 cats with skin lesions were examined microscopically by using 20% KOH and the methylene blue stain. Specimens were also inoculated in Sabouraud-chloramphenicol-cycloheximide agar. The hairbrush technique was performed in 200 cats with apparently healthy skin (120 of the urban and 80 of the rural area). Dermatophytes were isolated from 92 cats with skin lesions. M. canis was isolated from the 97,8% and T. mentagrophytes from 2,2% of the infected cats. Most of the infected animals (63) were up to 24 months old but the proportion between infected males and females cats was approximately equal. From the 120 cats of the urban area and the 80 cats of the rural area ( both groups included as apparently healthy cats) 40 (33,3%) and 15(18,7%) were found carrying dermatophytes, respectively. M. canis was exclusively isolated from the cats of the urban area ίη 70% while T. mentagrophytes in 15% and M. gypseum in 12,5%. The most frequent dermatophyte isolated from the apparently healthy cats of the rural area was M. gypseum (53,3%), while T. mentagrophytes (33,3%) and T. terrestre were the second and the third isolated. It is mentioned that infected cats and especially apparently healthy cats but carriers of M. canis, interfere with public health because of the possibility of transmission to human and given that numerous cases of children and of the animal owners have been affected.